Economic efficiency of agricultural enterprises in the system of organic farming - J. Jánský; I. Živělová; P. Novák (Agricultural Economics (AGRICECON), 2003)
The aim of this presentation is to introduce partial results of this research project aimed to the efficiency of businesses working with the organic systems. The proposal of mesures will be formed with the respect of results of analysis to support organic businesses, to increase organic land area corresponding with the progress in the EU and therefore to help to satisfy increasing demand for organic food, last but not least also to prove, that organic agriculture is truly functioning part of multifunctional agriculture.